2014
DOI: 10.1177/201010581402300112
|View full text |Cite
|
Sign up to set email alerts
|

Potential Applications of Spectral-Domain Optical Coherence Tomography (SD-OCT) in the Study of Alzheimer's Disease

Abstract: Alzheimer's Disease (AD) is the most common subtype of dementia. As the prevalence of dementia is projected to increase, the burden of the disease on society is expected to become increasingly significant. The link between eye pathology and neurodegenerative diseases has been established in multiple studies. In particular, optic nerve parameters associated with neuronal loss in AD include retinal ganglion cells (RGC). Retinal ganglion cells are similar to neurons in the cerebral cortex, and have been correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 68 publications
(83 reference statements)
0
12
0
Order By: Relevance
“…In addition, one study using SD-OCT showed a diffuse reduction of the RNFL and GCL combined in AD [49], although the authors were not able to determinate which layer was most affected by AD. Later studies have demonstrated IPL thinning in AD patients [41,50,52,56,57]. This reduction of ganglion cell complex thickness (GC-IPL and RNFL layers) in AD occurs to a larger extent than that accounted for age-related GC-IPL loss alone (about 0.3 μm/ year) [54].…”
Section: Pathological Changes In the Retina And Optic Nervementioning
confidence: 98%
See 4 more Smart Citations
“…In addition, one study using SD-OCT showed a diffuse reduction of the RNFL and GCL combined in AD [49], although the authors were not able to determinate which layer was most affected by AD. Later studies have demonstrated IPL thinning in AD patients [41,50,52,56,57]. This reduction of ganglion cell complex thickness (GC-IPL and RNFL layers) in AD occurs to a larger extent than that accounted for age-related GC-IPL loss alone (about 0.3 μm/ year) [54].…”
Section: Pathological Changes In the Retina And Optic Nervementioning
confidence: 98%
“…Increased cup-to-disc ratio has been reported to correlate with RNFL thinning in AD [40][41][42], and cup-to-disc ratio may be correlated with duration of disease [37]. This method, however, has certain disadvantages, as it is manual and highly subjective to each individual observer [41].…”
Section: Pathological Changes In the Retina And Optic Nervementioning
confidence: 99%
See 3 more Smart Citations